A Study of New Continuous Univariate Weibull Model with Empirical Illustrations - Rasheed, Hafiz Muhammad Kashif; Hussain, Sajid; Ali, Shafqat; Asghar, Muhammad; Bibi, Shazia; Khan, Abid (Scientific Inquiry and Review, 2024)
The theory of probability distribution is used for mathematical modeling in various research areas. It makes those models flexible that are used to quantify uncertainties and risks in extreme events. This is also important for decision-making. This study proposes a new model labeled as ‘exponentiated alpha Weibull (EAW)’. The densities and reliability functions of EAW are also depicted graphically. Various statistical properties of the proposed model are explored. For estimation, the maximum likelihood (ML) method is applied. Simulation study is also performed. To check model performance, the proposed model is compared with other competitive models (CMs) for water runoff data.